(untitled) (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: The incidence of type A aortic dissection (TAAD) has increased in several countries in recent decades, but epidemiological data for Switzerland are lacking. Furthermore, there are conflicting data regarding a gender-disparity with higher type A aortic dissection mortality in women. This study analysed sex-specific hospital incidence and in-hospital mortality rates of TAAD in Switzerland. METHODS: This study is a secondary data analysis of case-related hospital discharge data from the Swiss Federal Statistical Office for 2009–2018. Cases that were hospitalised and surgically treated for type A aortic dissection were included in this analysis. Standardised incidence rates were calculated using the European standard population in 2013. All-cause in-hospital mortality rates were calculated as raw values and standardised for age, sex, and the van Walraven comorbidity score. RESULTS: A total of 2117 participants were included in this study, of whom 67.1% were male. The age-standardised cumulative hospital incidence for type A aortic dissection treatment was 3.5 per 100,000 (95% CI: 3.3–3.7) for men and 1.7 (1.6–1.8) per 100,000 for women (p <0.001). The incidence rates increased in both sexes during the observed decade. The adjusted mortality rates for treatment of TAAD decreased from 27.6% (26.7–28.5%) in 2009 to 18.5% (17.9–19.1%) in 2018 in women, and they decreased from 19.0% (18.4–19.6%) to 12.3% (11.9–12.7%) in the same period in men. Multivariable logistic regression analysis revealed that female sex was significantly associated with higher mortality, with an odds ratio of 1.39 (1.07–1.79) (p = 0.012). CONCLUSIONS: Hospital incidence rates for the treatment of type A aortic dissection increased in both sexes over the observed decade. The mortality rate was significantly higher in women than it was in men, but it decreased in both sexes. TAAD remains a cardiovascular emergency with a high mortality rate even after emergency surgery.